EXPERIENCES OF EXPERTS INVOLVED IN THE IMPLEMENTATION OF THE EXTENDED PROFESSIONAL PROCEDURE FOR CHILDREN WITH PROBLEMS IN BEHAVIOR - Đurek Setinšek, Ivana; Majdak, Marijana (International Journal of Child, Youth and Family Studies, 2025)
The extended professional procedure (EPP) is carried out at primary schools as a special form of preventive work with children who manifest problems in their behavior and their primary environment. This paper aimed to investigate the experiences of experts — educators with backgrounds in social work, social pedagogy, or psychology, involved in the implementation of the EPP. We considered three research questions to investigate: (1) behavioral problems of children who participate in the EPP, (2) educators’ experiences with the implementation of the EPP, and (3) educators’ ideas for improving the program. For data collection, a qualitative focus group method was used, which included experts who have implemented the EPP; for data analysis, thematic qualitative analysis was used. The results show that children who were included in the EPP often manifested milder types of risky behaviors and usually came from families burdened with difficulties, a known risk factor for behavioral problems. Experiences of educators with the implementation of the EPP were both positive and negative. The negative aspects were mainly related to cooperation with the pedagogical service, social work institute, and parents, while the positive aspects were mainly related to the children’s perception of the program and the experts. The experts’ proposals and recommendations included improving the program by developing a clear definition of the EPP in both theory and practice, then paying strict attention to that definition.